Almost chosen people : oblique biographies in the American grain - Zuckerman, Michael, 1939- (University of California Press, 1993)
For a quarter of a century, Michael Zuckerman has been provoking - and sometimes almost seducing - his fellow historians to rethink their most cherished assumptions about the American past. Often he starts from a familiar figure or a hallowed interpretation. Always he disguises the familiar, hollows out the hallowed, rearranges what is left, provides a capacious but unexpected context, and emerges with a breathtakingly new conception of an old problem. In his effort to remake the meaning of the American tradition, Zuckerman takes the entire sweep of American history for his province. The essays in this collection - including two never before published and a new autobiographical introduction - range from early New England settlements to the corridors of modern Washington. Among his subjects are Puritans and Southern gentry, Benjamin Franklin and Benjamin Spock, Horatio Alger and Lewis Mumford, P.T. Barnum and Ronald Reagan. Writing of scammers and scoundrels, of racists and rebels, and of the purest genius, Zuckerman aims to capture the character of the country, its inner impulsion and its vagrant passions.